Optimal method of reducing harmonic content for Sinusoidal Pulse Width Modulation (SPWM) / Mohd Das Risin - Risin, Mohd Das (2009)
This project is focusing on optimizing harmonic content in Sinusoidal Pulse Width Modulation (SPWM) design. The results show that by varying number of bits, modulation index and switching frequency, the harmonic content to Total Harmonie Distortion (THD) can be analyzed and optimal method to reduce the harmonic content of TI ID can be found. This SPWM is designed using VHDL and implemented on ALTERA (DE2-70 board). The results, the SPWM waveforms and its Fast Fourier Transform (FFT) waveform, are measured using Digital Oscilloscope. The Total Harmonie Distortion (THD) is calculated from measured waveform. From the analysis, for 10 bit, mod index one and at frequency of 20 kHz, Total Harmonie Distortion for the SPWM design is optimized.